Hubungan Antara Kegiatan Tahsin Quran dan Kemampuan Membaca pada Teks Bahasa Arab Siswa Tahfid Pondok Ilyasiah As’adiyah Marang Kayu - Mustamin, Mustamin; Syarifaturrahmatullah, Syarifaturrahmatullah; Jannah, Lisa Ihdiatul (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
This study aims to examine the correlation between tahsin Al-Qur'an activities and the ability to read Arabic texts in male Tahfidz students at the Ilyasiyyah As'adiyah Islamic Boarding School Marangkayu. This research is a type of quantitative research with correlation techniques. Correlation technique is used to test the hypothesis in order to find the relationship between two variables. The subjects in this study were all male tahfidz students of class VII, VIII, and IX at the Ilyasiyyah As'adiyyah Islamic boarding school Marangkayu with a total of 32 respondents. Data collection used a questionnaire to determine the activities of tahsin Al-Qur'an (X) and used a language text reading test. Arabic to determine the ability to read Arabic text (Y). The research data that has been collected is then analyzed using statistical analysis techniques with the Product Moment formula. This study shows that: The activities of Tahsin Al-Qur'an owned by students are included in the